2011
DOI: 10.1002/bit.23055
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term immunologically competent human peripheral lymphoid tissue cultures in a 3D bioreactor

Abstract: Peripheral lymphoid organs (PLOs), the primary sites of development of adaptive immune responses, display a complex structural organization reflecting separation of cellular subsets (e.g. T and B lymphocytes) and functional compartments which is critical for immune function. The generation of in vitro culture systems capable of recapitulating salient features of PLOs for experimental, biotechnological and clinical applications would be highly desirable, but has been hampered so far by the complexity of these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…LECs can also attach to unwoven polyglycolic acid scaffolds [246]. In order to simulate lymph nodes, nonwoven polyamides, agarose matrix sheets, and macroporous cellulose microcarriers within an in vitro bioreactor have been utilized [247, 248].…”
Section: Techniques For Lymphatic Tissue Engineeringmentioning
confidence: 99%
“…LECs can also attach to unwoven polyglycolic acid scaffolds [246]. In order to simulate lymph nodes, nonwoven polyamides, agarose matrix sheets, and macroporous cellulose microcarriers within an in vitro bioreactor have been utilized [247, 248].…”
Section: Techniques For Lymphatic Tissue Engineeringmentioning
confidence: 99%
“…In terms of an in vitro attempt to create the human LN environment, it was demonstrated that antigen-specific B cell clusters could be observed in a bioreactor -an ex vivo culture device -containing a porous matrix with antigen-primed DCs (Giese et al 2006). Long-term human peripheral lymphoid tissue cultures with immunologically competence in a 3D bioreactor have been reported (Kuzin et al 2011). Potentially useful cell lines of artificial antigen-presenting cells (aAPC) were established for humans (Butler et al 2007).…”
Section: Attempts To Generate Human Peripheral Lymphoid Tissuesmentioning
confidence: 99%
“…Both of these approaches are being extended to immune organs – LNs, thymus, and BM – to create tools to elucidate immune cell interactions and the link to immune response and disease. This work has already identified matrix porosity, fluid flow, cytokine expression, and stromal cell interactions as important design parameters 17, 18, 19, 20, 21 .…”
Section: Immune Organoids and Organs-on-a-chipmentioning
confidence: 99%